THE CONCEPT OF ISLAMIC EDUCATION IN THE QAIDAH FIQHIYYAH - Mu’tasim Lidinillah; H.E. Mujahidin; Abas Mansur Tamam (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
This paper explains the principles of fiqhiyyah which are fundamentally a source of determining fiqh law based on the Qur'an and Sunnah, as well as because the nature of a rule is general so that it can be used also in solving problems that exist in the world of Islamic education, and also gave birth to the concept of Education by using 5 basic principles that are sourced from the Qur'an and Sunnah in the rules of fiqhiyyah. The method of writing this paper uses qualitative, descriptive, explanatory and comparative methods with a study approach to classical and modern Islamic literates, then compares them with the reality of the context of Islamic education and the problems that exist in the lives of Muslims today to give birth to the concept of Islamic education. Paper ini menjelaskan tentang kaidah fiqhiyyah yang secara mendasar sebagai sumber penetapan hukum fiqih yang berlandaskan al qur’an dan sunnah, begitu pula karena sifat dari sebuah kaidah adalah general sehingga bisa digunakan juga didalam memecahkan permasalahan-permasalahan yang ada didalam dunia pendidikan islam, dan juga melahirkan konsep Pendidikan dengan mengunakan 5 pokok kaidah dasar yang bersumber dari al-Qur’an dan Sunnah didalam kaidah fiqhiyyah. Metode penulisan paper ini menggunakan metode kualikatif, Deskriptif, eksplanatif dan Komparatif dengan pendekatan studi terhadap literatus-literatus Islam Klasik dan modern, kemudian menkomparasikannya dengan realitas konteks pendidikan islam dan permasalahan yang ada didalam kehidupan umat Islam saat ini untuk melahirkan konsep Pendidikan islam